2018
DOI: 10.1139/cjpp-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of aspirin against lipopolysaccharide-induced preeclampsia-like symptoms in rats by inhibiting the pro-inflammatory pathway

Abstract: Preeclampsia is an inflammatory disease and has connection with increased pro-inflammatory cytokines. Aspirin reduces the incidence of preeclampsia complications. However, the effects of aspirin on lipopolysaccharide-induced preeclampsia-like symptoms in rats have not been reported and the underlying molecular mechanism has not been illuminated. Hence, we investigated the anti-inflammatory effects of aspirin on lipopolysaccharide-induced preeclampsia-like phenotypes in pregnant rats and elucidated the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…And another report implied that TLR‐4/NF‐κB signaling pathway is involved in the development and pathogenesis of PE 40 . Consistent with previous studies, 8,9,18 we found an increase in placental TLR‐4 and NF‐κB expression in PE group. Importantly, AsIV treatment decreased TLR‐4 and NF‐κB protein expression in PE rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…And another report implied that TLR‐4/NF‐κB signaling pathway is involved in the development and pathogenesis of PE 40 . Consistent with previous studies, 8,9,18 we found an increase in placental TLR‐4 and NF‐κB expression in PE group. Importantly, AsIV treatment decreased TLR‐4 and NF‐κB protein expression in PE rats.…”
Section: Discussionsupporting
confidence: 91%
“…Beside the inflammation cytokines, in pregnant women with PE, antiangiogenic factor (soluble fms‐like tyrosine kinase‐1, sFlt‐1) is increased, whereas that of pro‐angiogenic factor (placenta growth factor, PIGF) is decreased 7 . Therefore, numerous studies have implied to employ angiogenic factors or inflammatory cytokines in the evaluation or diagnosis PE, 7 or even as a therapeutic target in the treatment of PE 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…69,70 Some studies have reported that aspirin may also prevent PE through anti-inflammatory effect by inhibiting the release of inflammatory factors in the placenta. 71,72 Recently, Li et al 73 investigated the impact of aspirin on gestational age advancement by metabolomics analysis and found that aspirin significantly slowed down metabolic gestational age by 1.27 weeks (95% CI: 0.66-1.88 weeks) in aspirin-treated high-risk women, compared to in those on placebo, and partially reversed various metabolic changes with the gestational age advancement.…”
Section: Prevention Of Preeclampsia With Aspirinmentioning
confidence: 99%
“…Therefore, active anti-inflammatory makes sense in the prevention of pre-eclampsia. Sun et al ( 33 ) found that aspirin could improve the PE symptoms induced by lipopolysaccharide by inhibiting the release of inflammatory factors in the placenta and serum. The anti-inflammatory mechanism of aspirin may be the inhibition of microRNA (miR)-155/ nitric oxide synthase axis and the reduction of inflammatory factor production.…”
Section: Mechanism Of Aspirin Use In Pre-eclampsiamentioning
confidence: 99%
“…Aspirin reduced the production of inflammatory cytokines (interferon-γ and interleukin-8). Enhanced antioxidant capacity (increased activities of superoxide dismutase, catalase, and glutathione peroxidase) and adhesion of human decidual mesenchymal stem cells in term pre-eclampsia ( 33 ). Animal experiments have confirmed that aspirin may also exert anti-inflammatory effects by inhibiting NF-κB p65/TLRs/MyD88 signaling pathway and reducing the production of interleukin-6, 1β, tumor necrosis factor-α and interferon-γ ( 35 ).…”
Section: Mechanism Of Aspirin Use In Pre-eclampsiamentioning
confidence: 99%